Dietary iron and vitamins in association with mortality. Issue 4 (April 2021) - Wang, Wenjie; Gao, Jian; Li, Na; Han, Shan; Wu, Lanlan; Zhang, Yunlong; Han, Tianshu; Shan, Ruiqi; Li, Ying; Sun, Changhao; Wu, Xiaoyan
Summary: Background & aims: Although disorders of iron metabolism are among the most common diseases and dietary intakes of vitamin A, B2, B6, C, E, and folic acid are known to affect the absorption or oxidation of iron, limited data are available on the association of dietary iron and these vitamins with mortality in the same population. Specifically, the holistic dietary vitamins intake and its combined effect with iron on mortality are unclear. The purpose of this study was to evaluate the association of dietary iron, holistic dietary vitamins, and their interactive effect with total and cause-specific mortality. Methods: We evaluated the effects of dietary total/heme/non-heme iron, vitamins, and their interaction on all-cause/cardiovascular disease (CVD)/cancer mortality among 14, 826 US adults in the National Health and Nutrition Examination Survey (NHANES), a population-based nationally representative study. We developed a vitamin score to represent the holistic dietary intakes of vitamin A, B2, B6, C, E, and folic acid. Results: A total of 2154 deaths occurred during a median follow-up of 9.3 years. Results from multivariate Cox proportional hazards models showed that higher vitamin score was associated lower risk of all-cause mortality ( P -trend = 0.027). Negative interactions between dietary heme iron and vitamin score were observed on all-cause/CVD mortality. Dietary higher vitamins combined with lower heme iron was associated with lower risk of all-cause and CVD mortality (HR (95% confidence intervals (CIs)): 0.80 (0.64–0.98) and 0.55 (0.31–0.98), respectively). Higher dietary vitamins combined with higher total/non-heme iron was associated with lower risk of CVD mortality (HR (95%CIs): 0.69 (0.48–0.99) and 0.70 (0.48–0.99), respectively). These results remained significant even excluding participants with iron supplementation. Conclusion: Our findings suggested that interactive effect of holistic dietary vitamins and iron play a protective role in decreasing all-cause and CVD mortality. Future studies, including cohort studies and clinical trials, are necessary to confirm these findings.